A comparative study of flow cytometry‐sorted communities and shotgun viral metagenomics in a Singapore municipal wastewater treatment plant. Issue 3 (28th July 2022) - Gu, Xiaoqiong; Yang, Yi; Mao, Feijian; Lee, Wei Lin; Armas, Federica; You, Fang; Needham, David M.; Ng, Charmaine; Chen, Hongjie; Chandra, Franciscus; Gin, Karina Yew‐Hoong
Abstract: Traditional or "bulk" viral enrichment and amplification methods used in viral metagenomics introduce unavoidable bias in viral diversity. This bias is due to shortcomings in existing viral enrichment methods and overshadowing by the more abundant viral populations. To reduce the complexity and improve the resolution of viral diversity, we developed a strategy coupling fluorescence‐activated cell sorting (FACS) with random amplification and compared this to bulk metagenomics. This strategy was validated on both influent and effluent samples from a municipal wastewater treatment plant using the Modified Ludzack–Ettinger (MLE) process as the treatment method. We found that DNA and RNA communities generated using bulk samples were mostly different from those derived following FACS for both treatments before and after MLE. Before MLE treatment, FACS identified five viral families and 512 viral annotated contigs. Up to 43% of mapped reads were not detected in bulk samples. Nucleo‐cytoplasmic large DNA viral families were enriched to a greater extent in the FACS‐coupled subpopulations compared with bulk samples. FACS‐coupled viromes captured a single‐contig viral genome associated with Anabaena phage, which was not observed in bulk samples or in FACS‐sorted samples after MLE. These short metagenomic reads, which were assembled into a high‐quality draft genome of 46 kbp, were found to be highly dominant in one of the pre‐MLE FACS annotated virome fractions (57.4%). Using bulk metagenomics, we identified that between Primary Settling Tank and Secondary Settling Tank viromes, Virgaviridae, Astroviridae, Parvoviridae, Picobirnaviridae, Nodaviridae, and Iridoviridae were susceptible to MLE treatment. In all, bulk and FACS‐coupled metagenomics are complementary approaches that enable a more thorough understanding of the community structure of DNA and RNA viruses in complex environmental samples, of which the latter is critical for increasing the sensitivity of detection of viral signatures that would otherwise be lost through bulk viral metagenomics. Abstract : This study elucidates the practical protocol of applying fluorescence‐activated cell sorting (FACS) and metagenomics on DNA and RNA viromes. This is the first systematic analysis of viral metagenomics in a municipal wastewater treatment plant with the Modified Ludzack–Ettinger (MLE) process. Coupling FACS with metagenomics improved the detection and genome assembly of certain rare viral species. In conclusion, bulk viral metagenomics and FACS‐coupled metagenomics delivered complementary results. Highlights: The practical protocol of applying fluorescence‐activated cell sorting (FACS) and metagenomics on DNA and RNA viromes. The first systematic analysis of viral metagenomics in a municipal wastewater treatment plant with Modified Ludzack–Ettinger (MLE) processes. Coupling FACS with metagenomics improved the detection and genome assembly of certain rare viral species. Bulk viral metagenomics and FACS‐coupled metagenomics delivered complementary results.